Conservation Trapped in Ethno-regional Politics: Multiple Faces of the Struggles over Nechisar National Park (Southern Ethiopia) - Bayisa Feye Bedane; Ann Cassiman; Mark Breusers (Conservation & Society, 2020)
The purpose of this study is to analyse the manifold struggles over land in southern Ethiopia's Nechisar National Park (NNP). The formal creation of NNP in 1974 fundamentally altered the scene, and congregated pastoralists, farmers, hunters, and conservationists in the struggles over resource access and use. While 'ancestral rights' continued to be invoked by those who had used the land previously, the NNP management and other actors could now call upon the imperatives of conservation to either curtail access to the Park and its resources or evict people from the Park. Following the downfall of the Derg regime in 1991, when Ethiopia adopted an ethnic federalism, attempts were made to assign a designated territory to each ethnic group. Thus, the struggles over NNP were further complicated by the renewal of the significance of ethnicity and the meanings of actors' strategies, given that the Park straddles the border between two regional states established under the new system of governance. This article is based on ethnographic fieldwork conducted in and around NNP. It demonstrates how attempts to introduce territoriality to hitherto unterritorialised spaces and ethnic groups resulted in the multiplication of the number of actors struggling for access to, and/or governance authority over, NNP and in the intensification of these struggles. The article argues for a shift in understanding people-park conflicts from a merely ecological and economistic approach to one that also situates these conflicts in the national politics of ethnic territorialisation.